Optimizing Suicide Prevention Programs and Their Implementation in Europe (OSPI Europe): an evidence-based multi-level approach - Gusmão, Ricardo Duarte Miranda de (2017)
BMC Public Health Hegerl, Ulrich Wittenburg, Lisa Arensman, Ella Van Audenhove, Chantal Coyne, James C. McDaid, David van der Feltz-Cornelis, Christina M. Gusmao, Ricardo Kopp, Maria Maxwell, Margaret Meise, Ullrich Roskar, Saska Sarchiapone, Marco Schmidtke, Armin Varnik, Airi Bramesfeld, Anke30 BIOMED CENTRAL LTD LONDON 528MX